Parameters Affecting F Wave Latency in Normal Population - Filiz Koc; Deniz Yerdelen (Çukurova Üniversitesi Tıp Fakültesi Dergisi, 2012)
Purpose: Determination of F-wave latency is a simple and valuable method in evaluating proximal part of the peripheral nerves. The aim of this study was to determine F-wave minimum latency of median, ulnar, tibial and peroneal nerves in normal healthy subjects. Methods: A total of 64 subjects including 34 female and 30 male at a mean age of 44.2 ± 16.3 (17-73) were studied. F-minimum latency was recorded from median, ulnar, peroneal and posterior tibial nerves using surface electrode. Collected data was evaluated according to the gender, age and height. Results: Age and height showed significant effect on F-wave minimum latency. However, gender showed nonsignificant effect on F-wave minimum latency. Conclusion: In evaluation of F latency, electrophysiological data of the cases should be interpreted after correcting for age and height. [Cukurova Med J 2012; 37(3.000): 168-171]